Comparison of the Effectiveness of Total Intravenous Anesthesia (TIVA) vs Inhalation Techniques in Patients with Morbid Obesity at Dr. M. Djamil General Hospital, Padang, Indonesia - Mutholib, Abdul; Zuriatinah (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Morbidly obese patients (BMI ≥ 40 kg/m²) present unique challenges in anesthesia. Total intravenous anesthesia (TIVA) and inhalation techniques have their respective advantages and disadvantages in this group of patients. This study aims to compare the effectiveness and safety of TIVA and inhalation anesthesia in morbidly obese patients at Dr. M. Djamil General Hospital Padang. Methods: A prospective, randomized study was conducted on 80 morbidly obese patients undergoing elective surgery. Patients were randomized to receive TIVA with propofol and remifentanil or inhalation anesthesia with sevoflurane and desflurane. Results: The TIVA group demonstrated faster recovery time (p = 0.02) and less postoperative opioid requirements (p = 0.01) than the inhalation group. There was no significant difference in the incidence of intraoperative or postoperative complications. Conclusion: TIVA is an effective and safe option for morbidly obese patients undergoing elective surgery. TIVA offers faster recovery and fewer postoperative opioid requirements than inhalation anesthesia.